KONTRIBUSI PERUSAHAAN TERHADAP PENDAPATAN DAN PENYERAPAN TENAGA KERJA MASYARAKAT LOKAL DI PERKEBUNAN TEH PT. RUMPUN SARI MEDINI KABUPATEN KENDAL - T D Sukarno; Dyah Mardiningsih; Tutik Dalmiyatun (Universitas Wahid Hasyim, 2017)
The purpose of this research are to identity the percentage of the corporate contribution to the level of employee’s household income and to identity the labor absorption that worked in PT. Rumpun Sari Medini. Method that been used in this research is survey. Data collection used observation, interviews, and questionnaires. The sampling method used stratified purposive sampling. Total respondent are 32 person, consists of 3 different employment status, which is permanent employee’s, freelancers, and tea leaves pickers. Data analyze uses quantitative descriptive and qualitative descriptive. The results of the research shows that corporate has 73% contribution of permanent employee’s monthly household income, 63,4% for freelancers and 40% for tea leaves pickers. Corporate absorb 78,8% of labor force in Medini Village, but the level of labor absorbtion in Ngesrepbalong district is just 7,3%.Keywords : Contribution, Income, Labor Absorption.